A closed form for the Stress Intensity Factor of a small embedded square-like flaw (Fracture and Structural Integrity, 2020)
In the present work, the stress intensity factor (SIF) of a small embedded square-like flaw is calculated by means of a procedure based on the Oore-Burns integral. An explicit equation is given to evaluate the SIF along the two axes of symmetry that correspond to the points where the SIF takes its maximum and minimum value on the contour crack. The SIF is calculated in accordance with FE numerical results.
Keywords: Weight function; Stress intensity factor; Three-dimensional crack; Weld